Political Recentralisation and the Diffusion of Solar Energy in China. Issue 7 (9th August 2019) - Chen, Geoffrey C.; Lees, Charles
Abstract: This article uses principal–agent theory to examine the governance of solar energy in China and question the notion of 'fragmented authoritarianism' in Chinese governance. It demonstrates that the governance of solar energy in China operates on two levels, with 'police patrol' control and monitoring mechanisms at the meso- or sectoral level combined with 'fire alarm' modes of political control at the micro-level. Drawing on original interview material, we argue that this two-level model and distinct set of supervisory institutions have allowed China, as a relatively late entrant into the solar energy sector, to address the growing environmental emergency within China and catch up technologically with the West.